Documentação semântica na gerência de projetos - Bastos, Erick Casagrande (2015)
The existence of project management supporting tools did not eliminate the need of using desktop documents in this domain. Text documents and spreadsheets are used in the context of projects, since they are instruments to record useful information to support communication between stakeholders and understanding about the project. However, one disadvantage of using documents is the difficulty of obtaining consolidated information from them, especially when information is distributed in several documents. The access to document content typically depends on human intervention, since they were originally created to be understood by humans and not by computers. To deal with this problem, Semantic Documentation can be used. Semantic Documentation consists in adding ontology-based metadata into desktop document content so that it become available for computers interpretation. In this work we explore the use of semantic documentation in project management aiming to support activities related to scope, time and cost management. We investigated the state-of-the-art of semantic documentation applied to project management by means of a systematic literature review. The results showed us that the research topic is recent and there are several aspects to be explored. As the infrastructure to the proposal presented in this work, we choose the Infrastructure for Managing Semantic Documents (IMSD) developed by Arantes (2010). IMSD uses domain ontologies as basis to semantic documentation, including features for content extraction, storage and search using semantic annotations. We extended IMSD by making it able to work with spreadsheets. Also, we specialized IMSD to the project management domain by creating features to support activities related to scope, time and cost management. For this, a domain ontology about software project management was developed and its concepts, relations and properties were explored. Lastly, we conducted a study that served as a preliminary evaluation of the proposal.